The use of various activities and techniques in teaching speaking (Eurasian Journal of Philology Science and Education, 2016)
Learners improve their speaking by interacting. Communicative language teaching based on real-life situations as well as collaborative learning serve best to reach this goal. By using this method, learners will have the essential opportunity of communicating in the target language. One of the main requirements is that ESL or EFL teachers should create an English speaking environment where students have real-life communication, activities, and tasks that promote oral language. This will occur when learners collaborate in small and big groups to complete a task and to achieve a goal. What are activities to promote speaking? Here is a brief description of the majority of these effective activities as well as some problems which the learners meet while learning the target language, and some techniques of solving these problems are given.
Keywords: real-life situation; scaffolding; active student involvement; brainstorming.